Coffee, Energy Drinks Consumption and Caffeine Use Disorder Among Law Enforcement College Students in Hungary - Ákos Erdős (European Journal of Mental Health, 2023)
Introduction: Caffeine is one of the most popular and consumed substances worldwide. The prevalence of caffeinated beverage consumption stands quite high among young people and in some professions, such as law enforcement. Aims: The aim of our study was to assess the lifetime and daily prevalence of caffeine consumption, the extent of consumption, and the prevalence of caffeine use disorder among law enforcement students. Methods: A cross-sectional, questionnaire-based survey was conducted among Hungarian law enforcement students at the University of Public Service (Hungary) Faculty of Law Enforcement (UPS FLE). The study sample (N = 180) consisted of 57.2% male (n = 103) and 42.8% female (n = 77). The Caffeine Use Disorder Questionnaire (CUDQ) was used to measure caffeine use disorder among law enforcement students. Results: The lifetime prevalence of caffeine consumption is 98.3% (n = 177) among law enforcement students. Two-fifths (n = 72) of law enforcement students are classified as daily consumers. The average caffeine intake of daily consumers was 177.5 mg/day (range: 60–550 mg/day; SD = 89.54). The majority (64.7%; n = 110) of caffeine users had experienced at least one symptom of caffeine use disorder in the past 12 months. Conclusions: This is the first study on caffeine consumption among Hungarian law enforcement students. Previous results suggest that the consumption of a high dose of caffeine could compromise aiming accuracy and shot placement, thereby jeopardizing the health and welfare of law enforcement personnel. Our results may be useful for researchers, Hungarian and foreign law enforcement agencies and law enforcement colleges, and vocational schools as well.